Request of utilization of BRAC's land - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the request of utilization of BRAC's land besides Jatrabari-Demra road to store tower crane components of BRACU new campus project.